Physical fitness of young Greco-Roman athletes under the restrictions of the COVID-19 pandemic - Ruslan Rusanov; Leonid Vostroknutov; Shi Ke; Katarzyna Prusik; Julia Golenkova (Pedagogy of Health)
Background and Study Aim. The physical training of young athletes is the basis for future success in competitions. Its effectiveness depends on many factors, among which safe conditions for life support stand out. In the context of the COVID-19 pandemic, there are significant restrictions on the training of young athletes. The aim of the study is the physical training of young Greco-Roman wrestlers in the context of the COVID-19 pandemic.